Individual Counseling Client-Centered Approach in Increasing the Resilience of Victims of Bullying - Fitri, Hartika Utami; Rasmanah, Manah; Kushendar, Kushendar; Hernisawati, Hernisawati (COUNS-EDU: The International Journal of Counseling and Education, 2022)
Resilience is an aspect that is owned by individuals in dealing with pressure or challenges. Individuals in health need Resilience. The hectic bullying among teenagers is a phenomenon that has not been fully resolved. This study aims to determine the effectiveness of individual counseling with the client-centred approach in increasing victim resilience-bullying. The methodology in this research is a quantitative experiment, design pre-experiment type and Post-experiment. The sampling technique in this study uses purposive sampling. The sample in this study was two respondents data analysis using Single Subject Research (SSR) with A design1-B-A2. The research results show that the resilience of bullying victims is classified as low with a score for respondent "A," which is 45 and respondent "R," namely 48. Both individual counseling approaches are client-centred and effective in increasing victim resilience-bullying given to respondents "A" and "R" turned out to be effective. With an increase of 14 points for respondent "A" and for respondent "R" as many as 15 points. Thus, the group counseling approach is client-centred and effective in increasing the resilience of victims of bullying.